Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) -13 + x = 39
x = 39 - (-13)
x = 52
b) 3x - (-17) = 14
3x + 17 = 14
3x = 14 - 17
3x = -3
x = -3 : 3
x = -1
c) x + 9.2 = 10
x + 18 = 10
x = 10 - 18
x = -8
a.-13+x=39
x=39+13=52
b.3x-(-17)=14
3x+17=14
3x=14-17=-3
x=-3:3=-1
c.x+9.2=10
x+18=10
x=10-18=-8
a) \(x-\left(-15\right)=-13-\left(-85-13\right)\)
\(\Leftrightarrow x+15=-13-\left(-98\right)\Leftrightarrow x+15=-13+98=85\)
\(\Leftrightarrow x=85-15=70\)
b) \(\left(-9-x\right)+\left(x-14\right)=17-\left(-8+x\right)\)
\(\Leftrightarrow-9-x+x-14=17+8-x\Leftrightarrow-23=25-x\)
\(\Leftrightarrow-23-25=-x\Leftrightarrow-x=-48\Leftrightarrow x=48\)
Tự kết luận
a. 9 - 35 = (17 - x) - (35 + 17)
=> -26 = 17 - x - 52
=> x = 17 - 52 + 26
=> x = -9
b. -7 - (12 + x) = -(-14 + 3) - (2x - 7)
=> -7 - 12 - x = - (-11) - 2x + 7
=> -19 - x = 11 + 7 - 2x
=> 2x - x = 18 + 19
=> x = 37
Đáp án là :
x = 26 .
x = -3 .
mk cho bài kham khảo nha
a) - 13 - x = 39
=> - x = 39 + 13
=> - x = 53
=> x = - 53
b) x - ( - 17 ) = 14
=> x + 17 = 14
=> x = 14 - 17
=> x = -3